2019
DOI: 10.34133/2019/2198906
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Lithium-Ion Diffusion in Layered Cathode Materials by Introducing Li + /Ni 2+ Antisite Defects for High-Rate Li-Ion Batteries

Abstract: Li+/Ni2+ antisite defects mainly resulting from their similar ionic radii in the layered nickel-rich cathode materials belong to one of cation disordering scenarios. They are commonly considered harmful to the electrochemical properties, so a minimum degree of cation disordering is usually desired. However, this study indicates that LiNi0.8Co0.15Al0.05O2 as the key material for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 45 publications
2
54
0
Order By: Relevance
“…This study suggests that novel migration channels of lithium ions can be generated by tuning the content of different phases in LiMn 0.5 Fe 0.5 PO 4 with the introduction of Li + /Fe 2+ antisite defects . In addition, the effect of Li + /Ni 2+ antisite defects on the properties of lithium ion diffusion in layered nickel‐rich cathode (LiNi 0.8 Co 0.15 Al 0.05 O 2 ) was analysed by Tang et al . The authors proposed that defective lithium ions with low valence in the nickel layer could weaken the repulsive interaction at the saddle point, and nickel ions with high valence in the lithium layer could push the neighbouring lithium ions by improved electrostatic repulsion.…”
Section: Factors Influencing Migration Of Lithium Ionsmentioning
confidence: 95%
See 4 more Smart Citations
“…This study suggests that novel migration channels of lithium ions can be generated by tuning the content of different phases in LiMn 0.5 Fe 0.5 PO 4 with the introduction of Li + /Fe 2+ antisite defects . In addition, the effect of Li + /Ni 2+ antisite defects on the properties of lithium ion diffusion in layered nickel‐rich cathode (LiNi 0.8 Co 0.15 Al 0.05 O 2 ) was analysed by Tang et al . The authors proposed that defective lithium ions with low valence in the nickel layer could weaken the repulsive interaction at the saddle point, and nickel ions with high valence in the lithium layer could push the neighbouring lithium ions by improved electrostatic repulsion.…”
Section: Factors Influencing Migration Of Lithium Ionsmentioning
confidence: 95%
“…The authors proposed that defective lithium ions with low valence in the nickel layer could weaken the repulsive interaction at the saddle point, and nickel ions with high valence in the lithium layer could push the neighbouring lithium ions by improved electrostatic repulsion. In their report, it was found that a proper concentration of Li + /Ni 2+ antisite defects (2.39 %) could improve the diffusion coefficient by one order of magnitude with superior rate capability (130 mAh g −1 at 10 C, 1 C=180 mA g −1 ) was observed in half cells prepared with Li/LiNi 0.8 Co 0.15 Al 0.05 O 2 …”
Section: Factors Influencing Migration Of Lithium Ionsmentioning
confidence: 99%
See 3 more Smart Citations